Frustrated and Aware: Knowing When Disagreement Is Deep - Kiš, Serhij (Informal Logic, 2025)
How do we know that we are in a deep disagreement – i.e. disagreement irresolvable by rational means? Some suggest, we know that only after trying out all our rational arguments. However, such strategy risks backfiring by polarizing the parties. This paper proposes an alternative way of recognizing depth. Drawing on epistemic capacity of emotions, I argue that debater’s emotional experience during deep disagreement, namely frustration, functions as an indicator of the disagreement’s depth.